2018
DOI: 10.1044/2017_ajslp-17-0002
|View full text |Cite
|
Sign up to set email alerts
|

Single-Word Speech Intelligibility in Children and Adults With Down Syndrome

Abstract: Results show age-related patterns in speech intelligibility in persons with DS and identify the contribution of dimensions of vowel production to intelligibility. The methods used clarify the phonetic basis of reduced intelligibility, with implications for assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
(56 reference statements)
2
35
0
Order By: Relevance
“…The percentage of in-telligible words produced by children with DS is variably reported, but Rupela et al (2016), in a study of seven children aged between 3;04 and 8;11, reported a range of between 26% and 89% compared with 91-99% for typically developing (TD) children aged between 2;11 and 5;01. Wild et al (2018) also found a difference between male and female speakers in a word-identification task. They report that whilst lay listeners correctly identified more than 40% of words produced by females with DS by age 9, male speakers did not reach this level until age 16.…”
Section: Introduction: Backgroundmentioning
confidence: 82%
See 4 more Smart Citations
“…The percentage of in-telligible words produced by children with DS is variably reported, but Rupela et al (2016), in a study of seven children aged between 3;04 and 8;11, reported a range of between 26% and 89% compared with 91-99% for typically developing (TD) children aged between 2;11 and 5;01. Wild et al (2018) also found a difference between male and female speakers in a word-identification task. They report that whilst lay listeners correctly identified more than 40% of words produced by females with DS by age 9, male speakers did not reach this level until age 16.…”
Section: Introduction: Backgroundmentioning
confidence: 82%
“…Wild et al . () also found a difference between male and female speakers in a word‐identification task. They report that whilst lay listeners correctly identified more than 40% of words produced by females with DS by age 9, male speakers did not reach this level until age 16.…”
Section: Introduction: Backgroundmentioning
confidence: 82%
See 3 more Smart Citations